DIPEPTIDYL PEPTIDASE-4 INHIBITORS: POTENTIAL FOR TREATMENT OF METABOLIC SYNDROME AND DEVELOPED FORMULATION APPROACHES - Mishra, Rakesh; Dhole, Shashikant (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This review article deals with the pre-clinical and clinical findings reviewed or investigated by the researchers on dipeptidyl peptidase-4 (DPP4) inhibitors as a potential in the treatment of metabolic syndrome. Most of the researchers reported the activity of DPP4 inhibitors in the management of obesity, hyperlipidemia, hypertension, atherosclerosis, and in cardiometabolic risk which are summarized in the article. This article also focuses on the formulation approaches in which the formulators have reported and used in the designing or development of DPP4 inhibitors as dosage form. The formulation approaches which are commonly employed on DPP4 inhibitors are immediate release, sustain release, and combination therapy.